一种基于路用性能的聚氨酯混合料配合比设计方法 (2024)
本发明涉及一种基于路用性能的聚氨酯混合料配合比设计方法，包括以下步骤：(1)选取矿质集料并确定其级配；(2)确定设计空隙率；(3)根据矿质集料的比表面积与设计的胶结剂膜的厚度，确定所用聚氨酯胶结剂的初始用量，并调整不同初始用量，制成不同的马歇尔试件与车辙试件；(4)以聚氨酯胶结剂的初始用量为横坐标，以马歇尔试件与车辙试件的路用性能为纵坐标，形成油石比性能坐标图，再通过平衡设计公式，得到最佳聚氨酯胶结剂用量；(5)检测最佳聚氨酯胶结剂用量下的聚氨酯混合料的路用性能是否合格。与现有技术相比，本发明不仅适用于传统混合料结构，同时也适用于单一粒径的混合料结构，整个设计流程简单，设计成本较低。 The invention relates to a polyurethane mixture mix proportion design method based on pavement performance. The method comprises the following steps of: (1) selecting mineral aggregates and determining the gradation of the mineral aggregates; (2) determining a designed void ratio; (3) according to the specific surface area of the mineral aggregates and the designed thickness of a cementing agent film, determining the initial dosage of a used polyurethane cementing agent, and performing adjustment to obtain different initial dosages to prepare different Marshall test pieces and rut test pieces; (4) forming an asphalt-aggregate ratio performance coordinate graph by taking the initial dosage of the polyurethane cementing